Antimicrobial drimane sesquiterpenes and their effect on endophyte communities in the medical tree Warburgia ugandensis - Drage, Sigrid; Mitter, Birgit; Muchugi, Alice; Jamnadass, Ramni H.; Sessitsch, Angela; Hadacek, Franz (Frontiers in Microbiology, 2014)
Metabolite profiles (GC–MS), drimane sesquiterpenes, sugars and sugar alcohols, were compared with bacterial and fungal endophyte communities (T-RFLP, DNA clones, qPCR) in leaves and roots of the pepper bark tree, Warburgia ugandensis (Canellaceae). Ten individuals each were assessed from two locations east and west of the Great Rift Valley, Kenya, Africa, which differed in humidity and vegetation, closed forest versus open savannah. Despite organ- and partially site-specific variation of drimane sesquiterpenes, no clear effects on bacterial and fungal endophyte communities could be detected. The former were dominated by gram-negative Gammaproteobacteria, Pseudomonadaceae and Enterobacteriaceae, as well as gram-positive Firmicutes; the fungal endophyte communities were more diverse but no specific groups dominated. Despite initial expectations, the endophyte community of the pepper bark tree did not differ from other trees that much.